Planeamiento del turismo y Geografía. Desarrollo en Cuba en los últimos 40 años - Estévez Pazó, R.; Del Risco Yera, Y.; Serrano Raffo, F. (Geographicalia, 2016)
Cuba in 90' decade, has been forced to developed the tourism as a means to improve to heal the serious situation of its economy. However, the activity is ilotnot new in the country. In the work it is approached like it has been the development of the tourism in Cuba, fundamentally in the last forty years, and the contributions that the geographical studies and planning for the best development in the same one.
Keywords: tourism; tourism management.